IMPLEMENTATION OF THE BASIC CONCEPTS OF LEARNING THAT HAPPENED IN THE ERA OF THE COVID-19 PANDEMIC - Maulida, Luthfia Nur (PROGRES PENDIDIKAN, 2021)
There are so many students who feel uneasy in the implementation of learning during the COVID-19 pandemic, many of them complain that the continuity of learning at home is severely hampered because of the use of gadgets that can plunge them into playing online games. As we know, not only students among students at school, but many students also protest because they feel bored and do not enter the material taught by lecturers if explained through zoom meetings as is usually used in learning media, this makes various parties feel confused, is it actually the students who are lazy or the educators who can't master teaching skills? There must be a survey that proves accurately at each educational institution so that both parties feel benefited and can change for the better. The author conducted research into several educational institutions to find out how many students feel they care about themselves and their education, especially education that will be the bridge for their future, if they don't understand from the bottom it will be difficult. The research method that the author will do is by sharing a link containing a Questionnaire which will later get answers from various parties, such as students who are still in Elementary School, Junior High School, High School, and Students who are currently studying in Higher Education. , by not requiring them to mention the name of the school and the institution they are currently undergoing in order to maintain the good name of the school and related institutions. If this is not sufficient, then the author has a plan B, namely by interviewing several people around in order to obtain more accurate and honest results which are directly conveyed by the mouth of the informant.